Major emerging vector-borne zoonotic diseases of public health importance in Canada - Kulkarni, Manisha A (Emerg Microbes Infect, 2015)
In Canada, the emergence of vector-borne diseases may occur via international movement and subsequent establishment of vectors and pathogens, or via northward spread from endemic areas in the USA. Re-emergence of endemic vector-borne diseases may occur due to climate-driven changes to their geographic range and ecology. Lyme disease, West Nile virus (WNV), and other vector-borne diseases were identified as priority emerging non-enteric zoonoses in Canada in a prioritization exercise conducted by public health stakeholders in 2013. We review and present the state of knowledge on the public health importance of these high priority emerging vector-borne diseases in Canada. Lyme disease is emerging in Canada due to range expansion of the tick vector, which also signals concern for the emergence of human granulocytic anaplasmosis, babesiosis, and Powassan virus. WNV has been established in Canada since 2001, with epidemics of varying intensity in following years linked to climatic drivers. Eastern equine encephalitis virus, Jamestown Canyon virus, snowshoe hare virus, and Cache Valley virus are other mosquito-borne viruses endemic to Canada with the potential for human health impact. Increased surveillance for emerging pathogens and vectors and coordinated efforts among sectors and jurisdictions will aid in early detection and timely public health response.